Exploring The Factors Influencing Customer Retention Through The Eyes Of Employees And Customers (Journal of Namibian Studies : History Politics Culture, 2023)
Customer retention stands as a cornerstone of business success, prompting organizations to explore multifaceted strategies to maintain a loyal clientele. This study takes a unique approach by examining the factors impacting customer retention through the perspectives of both employees and customers. Customer retention is a potentially beneficial strategy that banks may use to get a strategic advantage and sustain their operations in the current highly competitive banking landscape. This research has assessed the factors influencing customer retention and identified the key variables based on the viewpoints of both staff and consumers. A sample size of 125 clients from both public and commercial banks was selected for the purpose of this research.